A systematic review and meta-analysis of the reported symptoms of Covid 19 in pregnancy - H.S.O. Abduljabbar; H. Abduljabar (Clinical and Experimental Obstetrics & Gynecology)
Introduction: The percentage of Symptomatic pregnant and non-pregnant women infected with Covid 19 is the same. The common symptoms in pregnant women are cough, fever, sore throat and myalgia. The objective of this is systematic review and meta-analysis of the commonly reported symptoms of COVID 19 in pregnancy and to compare it to non-pregnant. Methods: Study Design; Systematic review and meta-analysis of published retrospective studies. Searches conducted from December 2019 - April 2020 on PubMed. Medline, EMBASE, ISI Web of Science Electronic database used to collect data, corresponding to the (PRISMA) Preferred Reporting Items for Systematic Meta-Analysis, using the following search terms: keywords "coronavirus, COVID-19, pregnancy". Results: Figure 1 presents the study flow diagram. We identify 114 records through database searching, sixteen further studies recognized through other sources, and 98 papers isolated after duplicates, leaving 32 reports. After screening for titles and abstracts, we found only 27 reports to be potentially suitable and rescued these reports in full text. We excluded seven studies; 20 did not report symptoms of groups of interest. In the process of Screening, 16 were screened. Ten of full-text articles assessed for appropriateness, six full-text articles omitted with reasons, and only Four studies [12-15] were included in the review. Conclusion: The only symptoms that are more common in pregnant than non-pregnant are the sore throat. That concluded that when pregnant women start to have sore throat care should be taken to exclude COVID-19 infection.